MODERATION IN UNDERSTANDING HADITH ABOUT RELIGIOUS EXTREMISM FROM THE PERSPECTIVE OF YUSUF QARDHAWI - Faruq, Umar; Warsito, Lukisno Choiril (UIN Mataram, 2023)
It is important to know the hadith as an explanation of the Qur'an and to understand the hadith in a moderate way to get a complete and not excessive understanding, so that it is far from extreme practices and there are no fault in understanding the text of the hadith that is used as a guide so that it is necessary to carry out an analysis in various ways. approach in understanding a hadith, this paper aims to understand the hadith about religious extremes using Yusuf Qardhawi's perspective of moderation reasoning. The method used is the approach and reasoning analysis of Yusuf Qardhawi in understanding the hadith in a moderate manner so that it can be concluded that the hadith about religious extremes is in accordance with the instructions of the Qur'an and there are no verses of the Qur'an that contradict the hadith, as well as several There is no contradiction in the themes of the hadith, so there is no need to merge or interpret. It is also very important to look at the background of the descent of a hadith, such as in extreme religious traditions where asbabul wurud is prohibited even if it is limited to taking the jumrah stone, which indicates that excessive and even extreme actions are prohibited, this is in accordance with the principles of religious moderation according to Yusuf Qardhawi, namely: implement a moderate attitude that is between extreme movements and fundamentalism.